2021
DOI: 10.3390/cryst11020092
|View full text |Cite
|
Sign up to set email alerts
|

Using a Modified Polyamidoamine Fluorescent Dendrimer for Capturing Environment Polluting Metal Ions Zn2+, Cd2+, and Hg2+: Synthesis and Characterizations

Abstract: One of the most pressing global concerns is how to provide a clean environment for future generations given the exacerbation of urban, agricultural, industrial, and economic activities due to the escalating size of the global population. A polyamidoamine (PAMAM) dendrimer peripherally modified with 4-N,N′-dimethylethylenediamine-1,8-naphthalmide as a chromophore was synthesized and utilized to capture hazardous heavy metal ions. This modified fluorescent dendrimer (FCD) was complexed with Group 12 metal ions (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 92 publications
0
16
0
Order By: Relevance
“…The choice was to investigate these four AMR genes due to their most frequently detection when ESBL/AmpC E. coli was isolated not only in dogs [5,17,[20][21][22] but also in other animal species [31][32][33] as well as in humans [34][35][36]. Concerning our study area, the only data currently available about the presence of these resistant genes in ESBL/AmpC E. coli are those from a study on wild boar and even in that wild species bla CTX-M was the most frequently detected with a prevalence of 12.3% (185/1504) followed by bla TEM (6.98%, 105/1504), bla CMY (0.86%, 13/1504) and bla SHV (0.47%, 7/1504) [37]. In this regard, focusing on the spread of AMR genes in humans, during 1990s, the most ESBLs were mutants of the classical TEM-1, -2 and SHV-1 enzymes [38] and bla TEM was the most frequent isolated among nosocomial strains [39].…”
Section: Discussionmentioning
confidence: 99%
“…The choice was to investigate these four AMR genes due to their most frequently detection when ESBL/AmpC E. coli was isolated not only in dogs [5,17,[20][21][22] but also in other animal species [31][32][33] as well as in humans [34][35][36]. Concerning our study area, the only data currently available about the presence of these resistant genes in ESBL/AmpC E. coli are those from a study on wild boar and even in that wild species bla CTX-M was the most frequently detected with a prevalence of 12.3% (185/1504) followed by bla TEM (6.98%, 105/1504), bla CMY (0.86%, 13/1504) and bla SHV (0.47%, 7/1504) [37]. In this regard, focusing on the spread of AMR genes in humans, during 1990s, the most ESBLs were mutants of the classical TEM-1, -2 and SHV-1 enzymes [38] and bla TEM was the most frequent isolated among nosocomial strains [39].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of endometriosis is largely unknown. Previous research has shown that endometriosis is prevalent after menarche and dramatically drops after menopause, which has led researchers to believe that the disorder is estrogen-and progesterone-dependent [26,27,29].…”
Section: Endometriosis 21 Definition Epidemiology and Classificationmentioning
confidence: 99%
“…The DSB ends are firstly resected by the MRN ( Mre11–Rad50–Nbs1 ) complex with EXO1 , DNA2, and MUS8 , leading to the development of the ssDNA and pushing the cells towards HR [ 92 , 93 ]. Subsequently, the resected DNA ends are coated by the hyperphosphorylated single-stranded DNA binding protein A (RPA) [ 94 , 95 ]. The variant H2AX is stimulated and phosphorylated by apical kinases, such as ATM and ATR (ATM and Rad3-related).…”
Section: Parp Inhibitor Resistancementioning
confidence: 99%